Analisis Studi Kelayakan Bisnis Usaha Aksesoris Gelang Handmade ASD Aksesoris - Mohamad Afrizal Miradji; Mohammad Ilham Ardiansyah; Surti Padu Leba; Diva Isabella Feoh; Fransiskus Didianus Saputra (Journal of Economics, Management, and Accounting, 2026)
This study aims to analyze the business feasibility of ASD Aksesoris, a handmade bracelet accessories enterprise, as part of the development of sustainability-oriented micro-enterprises. The research is grounded in the growing consumer interest in handmade accessories that offer aesthetic value, distinctive designs, and personalized character, which necessitates a comprehensive assessment of business feasibility prior to further expansion. The study employs a qualitative descriptive approach using a business feasibility analysis that encompasses market and marketing aspects, technical and operational aspects, as well as financial aspects, drawing on official reports and the enterprise’s actual operating conditions. The findings indicate that ASD Aksesoris possesses considerable market potential, supported by clear consumer segmentation and flexible marketing strategies. From an operational perspective, the production process is assessed as efficient and relatively easy to manage, while from a financial standpoint the business demonstrates the ability to generate profits with a relatively low level of financial risk. Overall, ASD Aksesoris is deemed feasible to operate and to further develop.